2021
DOI: 10.1037/aca0000345
|View full text |Cite
|
Sign up to set email alerts
|

Drawing portraits and still lifes from 2D and 3D sources.

Abstract: Drawing is hard, and portraits especially so. To characterize what is hard or easy about it, 258 charcoal drawings, completed in real-world conditions from photographs (two-dimensional, 2D) and from direct observation of the same subjects (three-dimensional, 3D), were assessed both subjectively and objectively. There was no difference between drawings made from 2D and 3D in their subjectively rated accuracy or quality, or their objectively measured geometric accuracy. However, the semantic contentportraits ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Some individuals may be particularly adept at drawing from photographs but may use different approaches when drawing from real life. However, other studies have shown that when participants are asked to draw from photos and real life, they do not show significant differences in their drawing quality (L. Carson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals may be particularly adept at drawing from photographs but may use different approaches when drawing from real life. However, other studies have shown that when participants are asked to draw from photos and real life, they do not show significant differences in their drawing quality (L. Carson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals may be particularly adept at drawing from photographs but may use different approaches when drawing from real life. However, other studies have shown that when participants are asked to draw from photos and real life, they do not show significant differences in their drawing quality (L. Carson et al, 2021). Thus, the use of a photograph for the drawing task may not necessarily interfere with assessing the relationship between visuospatial reasoning and drawing skills.…”
Section: Other Limitationsmentioning
confidence: 98%